I assume by f¹, you actually mean f⁻¹ as in the inverse of f. I also assume you are asked to find f(x) (as in the inverse of f⁻¹) and f⁻¹(4).
Given that
![f^(-1)(x+2) = (x-1)/(x+1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/dhe7en2ogheg29rzhih99cpo7y2mkpepae.png)
with x ≠ 1, we can find f⁻¹(x) by replacing x + 2 with x :
![f^(-1)(x + 2) = (x-1)/(x+1) = ((x+2) - 3)/((x + 2) - 1) \implies f^(-1)(x) = (x-3)/(x-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/q7yl7joaifkmo6kn4xrd7uqkha5o9yund3.png)
Then when x = 4, we have
![f^(-1)(4) = (4-3)/(4-1) = \frac13](https://img.qammunity.org/2023/formulas/mathematics/high-school/iyy0ustbc5yfdit4nkmvad1phl9u6rhp65.png)
Of course, we also could have just substituted x = 2 into the definition of f⁻¹(x + 2) :
![f^(-1)(4) = f^(-1)(2+2) = (2-1)/(2+1) = \frac13](https://img.qammunity.org/2023/formulas/mathematics/high-school/i7y1jvqolnpvothttia9ekanwj66fthyt3.png)
To find f(x), we fall back to the definition of an inverse function:
![f^(-1)\left(f(x)\right) = x](https://img.qammunity.org/2023/formulas/mathematics/high-school/98i6891q30vtdjg4dc4pa723h1pqmzp6d1.png)
Then by definition of f⁻¹, we have
![f^(-1)\left(f(x)\right) = (f(x)-3)/(f(x)-1) = x](https://img.qammunity.org/2023/formulas/mathematics/high-school/6b7xydr3nkxt4ag9385hwglgxi8az63dou.png)
Solve for f :
![f(x) - 3 = x (f(x) - 1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/3wndvhj7d989ss2bj23npbwveja6fjqbgd.png)
![f(x) - 3 = x f(x) - x](https://img.qammunity.org/2023/formulas/mathematics/high-school/le9m4ka15ms6ai0ellrbiawx7ss7qkqns5.png)
![f(x) - x f(x) = 3 - x](https://img.qammunity.org/2023/formulas/mathematics/high-school/ga30xw4g8wtg16u5h1uyub25s6pmf7k4v9.png)
![(1 - x) f(x) = 3-x](https://img.qammunity.org/2023/formulas/mathematics/high-school/cix09a2u93kzl4eq4qz30maqco4eowmyxb.png)
![f(x) = (3-x)/(1-x) = (x-1)/(x-3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/i2l4i6qdqm40rol6i519fjy99u82mszcfp.png)